2019
DOI: 10.1186/s12879-019-4266-y
|View full text |Cite
|
Sign up to set email alerts
|

Spread and clinical severity of respiratory syncytial virus A genotype ON1 in Germany, 2011–2017

Abstract: Background The Respiratory Syncytial Virus (RSV) A genotype ON1, which was first detected in Ontario (Canada) in 2010/11, appeared in Germany in 2011/12. Preliminary observations suggested a higher clinical severity in children infected with this new genotype. We investigated spread and disease severity of RSV-A ON1 in pediatric in- and outpatient settings. Methods During 2010/11 to 2016/17, clinical characteristics and respiratory samples from children with acute respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Genotyping of the strains showed that one single ge­notype per subtype was detected, and RSV-A ON1 predominated during 2016–2017, and RSV-B BA predominated in the next season. Similarly, in Germany, a predominance of RSV-A (53.2%) was seen during 2016–2017, with ON1 being the only genotype detected [19]. However, the predominance of RSV subtypes in other European countries during the same winter seasons varied.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the strains showed that one single ge­notype per subtype was detected, and RSV-A ON1 predominated during 2016–2017, and RSV-B BA predominated in the next season. Similarly, in Germany, a predominance of RSV-A (53.2%) was seen during 2016–2017, with ON1 being the only genotype detected [19]. However, the predominance of RSV subtypes in other European countries during the same winter seasons varied.…”
Section: Discussionmentioning
confidence: 99%
“…In countries of temperate zones, upper respiratory tract infections being more frequent in autumn and spring, rising during winter, following weather changes [ 11 ]. A study conducted in Germany suggests that humidity and temperature are associated with hospitalizations due to lower respiratory tract infections by the Influenza virus, RSV, and RV [ 12 ]. Another study carried out in the Colombia, showed that the occurrence of acute respiratory infection in children was associated with air temperature and relative humidity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…to assess the adaptive mechanisms and virus clearance (Fig 6A). Additionally, neonates were infected with RSV-ON1-H1 strain, a primary clinical isolate recently circulating in central Europe (see following section) [36]. BAL cellularity is provided in S8 Fig; no significant difference was found between the absolute counts of RSV-infected adults and neonates.…”
Section: Neonates and Adults Are Mounting A Distinct Pulmonary T Cell Response Following Rsv A2 Infectionmentioning
confidence: 99%
“…While immune-mediated mechanisms are central determinants of RSV severity, there are indications that viral factors play also a role [37]. We evaluated the pulmonary T cell response in neonates infected with RSV A2, a well characterized prototypical strain of RSV, in comparison to the RSV-ON1-H1, a primary clinical isolate which was the major genotype circulating in central Europe during the RSV seasons of 2012 to 2017 (Fig 6A) [36]. Whereas infection of neonates with RSV-ON1-H1 strain led to a milder disease, as indicated by milder histological lesions (Fig 8A ), the viral loads and virus clearance was comparable between both strains, again reinforcing the hypothesis for immune-mediated RSV pathogenesis (Fig 8B).…”
Section: The Severity Of Rsv Disease Relates To the Magnitude Of The Bronchoalveolar T Cell Responsesmentioning
confidence: 99%